The Effect of Learning Motivation and Science Literacy Skills on The Higher-Order Thinking Skills of High School Students in Maros District - Marwah Mahmud; Firdaus Daud; Muhammad Junda; Syamsiah; Yusminah Hala (PT. Global Research Collaboration, 2026)
The ability to think critically, analyze information, and solve problems has become an important aspect of learning in the 21st century. However, students’ Higher Order Thinking Skills (HOTS) are not developed solely through classroom instruction and may be influenced by other factors, including learning motivation and scientific literacy. This research examined the contribution of learning motivation and scientific literacy to the HOTS of Grade XII students in public senior high schools in Maros Regency. An ex post facto design with a quantitative approach was employed. Data were collected using a learning motivation questionnaire, a scientific literacy test, and a HOTS test. The data were subsequently analyzed through descriptive statistics and multiple linear regressions. The analysis showed that learning motivation, scientific literacy, and HOTS were generally at a moderate level. Regression testing demonstrated that learning motivation and scientific literacy jointly contributed significantly to HOTS. Similar results were obtained from the partial analysis, where each variable showed a positive and significant contribution. Among the two predictors, scientific literacy accounted for a greater contribution to students’ HOTS. These results suggest that strengthening students’ scientific literacy alongside maintaining their learning motivation may support the development of higher-order thinking skills in science learning.